2021
DOI: 10.22271/phyto.2021.v10.i2m.13925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing dates and varieties of sesame (Sesamum indicum L.) for higher productivity during pre-kharif season in New Alluvial Zone of West Bengal

Abstract: In the context of optimizing sowing dates and varieties for realizing higher productivity notably for sesame an experiment with varying sowing dates and varieties was executed under the climatic scenario of New Alluvial Zone of West Bengal. The experimental findings reveal that crop sown on 15th March (2017) recorded highest seed yield (760.1 kg/ha.), which was 3.4, 3.9 and 18.3% higher than the sowing time of 1 st March, 1 st April and 15 th February , respectively during 2017. Among the three varieties, Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The interaction of varieties and different dates of sowing was however non-significant with regard to this parameter. Several researchers also reported early flowering with regard to white seeded sesame (Saju Adhikary et al, 2021) and second fortnight of December which clearly indicted the adoption and suitability of white seeded sesame when temperatures were low in the month of December in comparison to brown seeded types of sesame.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The interaction of varieties and different dates of sowing was however non-significant with regard to this parameter. Several researchers also reported early flowering with regard to white seeded sesame (Saju Adhikary et al, 2021) and second fortnight of December which clearly indicted the adoption and suitability of white seeded sesame when temperatures were low in the month of December in comparison to brown seeded types of sesame.…”
Section: Resultsmentioning
confidence: 96%
“…Several researchers also reported higher number of branches with brown seeded sesame and second fortnight of December which indicated that the branches per plant reduced with delay in sowing which might be attributed increased soil temperatures and pest and disease infestation and increased mean temperature during crop growth period. Several researchers also reported highest branches per plant with regard to brown seeded sesame over white seeded types and decreased branches per plant with late sowing (Saju Adhikary et al, 2021). Delay in planting decreases the number of branches per plant and number of capsules per plant according to Ahmed et al (2009).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation